Psychophysiological responses to treadwall and indoor wall climbing in adult female climbers - Baláš, Jiří; Gajdošík, Jan; Krupková, Dominika; Chrastinová, Leona; Hlaváčková, Alžběta; Bačáková, Radka; Giles, David (Scientific reports, 2021)
The purpose of the study was to compare the psychophysiological response of climbers of a range of abilities (lower grade to advanced) when ascending identical climbing routes on a climbing wall and a rotating treadwall. Twenty-two female climbers (31.2 ± 9.4 years; 60.5 ± 6.5 kg; 168.6 ± 5.7 cm) completed two identical 18 m climbing trials (graded 4 on the French Sport scale) separated by 1 week, one on the treadwall (climbing low to the ground) and the other on the indoor wall (climbing in height). Indirect calorimetry, venous blood samples and video-analysis were used to assess energy cost, hormonal response and time-load characteristics. Energy costs were higher during indoor wall climbing comparing to those on the treadwall by 16% (P < 0.001, [Formula: see text] = 0.48). No interaction of climbing ability and climbing condition were found. However, there was an interaction for climbing ability and post-climbing catecholamine concentration (P < 0.01, [Formula: see text] = 0.28). Advanced climbers' catecholamine response increased by 238% and 166% with respect to pre-climb values on the treadwall and indoor wall, respectively; while lower grade climbers pre-climb concentrations were elevated by 281% and 376% on the treadwall and indoor wall, respectively. The video analysis showed no differences in any time-motion variables between treadwall and indoor wall climbing. The study demonstrated a greater metabolic response for indoor wall climbing, however, the exact mechanisms are not yet fully understood.
Keywords: sportovní výkon; Psychophysiology; Hand Strength; Female; psychofyziologie; dospělí; síla ruky; Adult; Athletic Performance; Heart Rate; Humans; ženské pohlaví; srdeční frekvence; lidé; horolezectví; Mountaineering; Oxygen Consumption; spotřeba kyslíku